Malay epic and historiography literature students' perception towards interface design elements - Noor Muhammad, Salmah Jan; Jasni, Khairul Zainie (Canadian Center of Science and Education, 2018)
The interface is an important element in delivering information. This is because the interface becomes an early attraction to the user's perception before going to the next level. A good interface design will emphasize easy and user-friendly elements. Unfriendly interface design may impact the activity provided. This study aims to identify, parse and analyze user ratings on interface design. The respondents of the study involved 87 BBK 3311 Malay Epic and Historiography Literature at Universiti Putra Malaysia. The emphasis of this study will focus on nine interface design elements. The quantitative approach is used to carry out this study. A questionnaire instrument specifically designed to assess respondents' assessment of the interface design. This survey is available online using the Survey Monkey website and analyzed based on the Technology Acceptance Model (TAM) approach. This is because this approach is specifically designed to analyze the acceptance of the technology. The results of the study showed the level of tendency of students to be interested in the interface design. The results of the study can also help in giving an overview to the online course builder on the interface design that affects students' interest. Furthermore, it is hoped that the results of this study will be a guideline in building interface designs in the website.